Influences on the cold start behaviour of a diesel engine at reduced compression ratio - MacMillan, David James (2009)
The design trend for light duty diesel engines is towards lower compression ratio and higher turbocharger boost. This can enable higher specific power and lower pollutant emissions to be achieved, but raises concerns that cold start operation might be adversely affected. This is investigated and quantified through the study of a modern light duty diesel engine at two compression ratios and temperatures down to -20ºC.